The Transportation and Storage Conformity Evaluation of Hazardous and Toxic Waste of Fertilizer Production : (A case Study in Industry X of West Indonesia) - Aulia Nur Mustaqiman; Erland Aldi Hutta (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Industry X is one of the sectors of the fertilizer and chemical industries that produce ammonia and urea. Their factory has a mass production that also makes them produce a huge amount of waste, especially Hazardous and Toxic Waste (B3 in Indonesian abbreviation). The resulting hazardous waste hereinafter referred to B3 Wastes, will then be managed under the applicable laws and regulations. The management of B3 wastes starts from the source and the producer of B3 wastes, temporary storage (TPS LB3 and TPS Fly Ash and Bottom Ash), waste labelling, and the generation of B3 wastes. This study aim (1) to recognize the condition of B3 in Industry X, (2) to identify kind of B3 waste in Industry X, and (3) to evaluate the operational of B3 packaging and labelling, The researchers will hold an observation, literature study, interview, and discussion as the data collection methods. Additionally, the analysis of the results and discussion of this study uses qualitative descriptions.